Novel Biologically Active Triterpenoid Saponin from the Leaves of Xanthium strumarium Linn. - YADAVA, R.N.; JHARBADE, JITENDRA (Asian Journal of Chemistry, 2010)
A novel triterpenoid saponin, 3-O[α-L-rhamnopyranosyl-(1→3)-O-β-D-xylopyranosyl]maniladiol has been isolated from the leaves of Xanthium strumarium. Its structure was determined by various spectral analysis and chemical degradations. This compound shows antiinflammatory activity.